11 Targeting 11β-HSD1 to promote angiogenesis – consequences for solid tumour growth. (1st April 1997) - Davidson, Callam; Muir, Morwenna; Homer, Natalie; Andrew, Ruth; Brunton, Val; Hadoke, Patrick WF; Walker, Brian R
Abstract : 11β-Hydroxysteroid dehydrogenase type 1 (11β-HSD1), which generates active glucocorticoids from inactive precursors, is expressed in glucocorticoid target tissues, including the arterial wall. Since active glucocorticoids are anti-angiogenic 11β-HSD1 inhibitors enhance angiogenesis and may have therapeutic potential in ischaemia. However increased angiogenesis may be detrimental in tumours. This investigation tested the hypothesis that 11β-HSD1 inhibition promotes angiogenesis and tumour growth in mouse models of squamous cell carcinoma (SCC) and pancreatic ductal adenocarcinoma (PDA). Murine tumour cells (1 × 10 6 ) were injected subcutaneously into mice (female, 10–12 weeks, FVB/C57Bl6/J) receiving RM-1 diet with, or without (Control), the 11β-HSD1 inhibitor UE2316 (175 mg/kg). Tumour size was measured every 2–3 days for 2–3 weeks. Sections of tumours were stained for vascular markers (CD31, alpha-smooth muscle actin) for quantification of vessel density. Steroid/drug levels were measured in plasma/tissues using liquid chromatography tandem mass spectrometry whilst 11β-HSD1 activity was assayed in tissue homogenates by high performance liquid chromatography. The effects of 11β-HSD1 inhibition on angiogenesis were examined ex vivo using an aortic ring assay. Data are mean±SEM. 11β-HSD1 inhibition increased SCC tumour growth in FVB mice (p<0.01) but did not affect the growth of PDA tumours in C57Bl6/J mice. Vessel density was unaffected in both tumour types. SCC tumours expressed more 11β-HSD1 mRNA and had higher (p<0.001) enzyme activity (0.291±0.054 nmoles product/mg/min) than PDA tumours (0.038±0.006). FVB mice had higher plasma UE2316 levels than C57Bl6/J mice (164.6±78.28 nM vs 14.4±6.23 nM), and reduced circulating corticosterone after UE2316 treatment. UE2316 reduced type 1 collagen in SCC tumours (9.8±0.8 vs 3.8%±0.6% area, p<0.001). Pharmacological inhibition of 11β-HSD1 did not alter steroid-mediated angiostasis in aortic rings. 11β-HSD1 inhibition does not promote angiogenesis in SCC or PDA tumours, but may increase SCC growth through a mechanism involving reduced fibrosis. Whether 11β-HSD1 inhibition increases angiogenesis in glucocorticoid-sensitive tumours remains to be established.